2020
DOI: 10.3390/cancers12030536
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of the Anti-Kinase Activity of the IDH1 Inhibitors

Abstract: Isocitrate dehydrogenases constitute a class of enzymes that are crucial for cellular metabolism. The overexpression or mutation of isocitrate dehydrogenases are often found in leukemias, glioblastomas, lung cancers, and ductal pancreatic cancer among others. Mutation R132H, which changes the functionality of an enzyme to produce mutagenic 2-hydroxyglutarate instead of a normal product, is particularly important in this field. A series of inhibitors were described for these enzymes of which ivosidenib was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The change in this transcript’s level was related to the influence of the sulfonic styrylquinazolines on the overall cellular metabolism and the inhibition of cell proliferation and growth. This is supported by several reports, which revealed the potency of the sulfonamide analogs as mutant IDH1 or dual IDH1/ABL inhibitors [ 32 , 59 , 60 ]. It is worth noting that a decreased IDH1 expression may prevent the overproduction of onco-metabolites, which can usually positively regulate the HIF pathways that are involved in angiogenesis, invasion and metastasis [ 61 ].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The change in this transcript’s level was related to the influence of the sulfonic styrylquinazolines on the overall cellular metabolism and the inhibition of cell proliferation and growth. This is supported by several reports, which revealed the potency of the sulfonamide analogs as mutant IDH1 or dual IDH1/ABL inhibitors [ 32 , 59 , 60 ]. It is worth noting that a decreased IDH1 expression may prevent the overproduction of onco-metabolites, which can usually positively regulate the HIF pathways that are involved in angiogenesis, invasion and metastasis [ 61 ].…”
Section: Resultssupporting
confidence: 72%
“…Interestingly, all of the compounds interacted with the BTK and Lck kinases in an inhibition range from 9% to 43% (see in Table 2 ). It is worth noting that oncogenic BTK kinase is highly expressed in leukemia cells, which may explain the susceptibility of these cells to the tested compounds to some degree [ 32 , 33 ]. Moreover, several reports have shown that BTK kinase is an important element of the cascade of the signal transduction from BCR-ABL through Lyn and Syk, which leads to calcium release, cell proliferation and the activation of the NF-κB pathway [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…We chose these two cell lines because of their characteristics, including high levels of BTK expression, as reported previously. 32,33 The tested nanomaterial resulted in good antiproliferative activity against RAJI cells. The calculated IC 50 parameter was 350 µM (Figure 4A).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Chelating metal ions can be a promising approach to designing novel and effective anticancer drugs. In our recent work, several scaffolds were evaluated for their potency as biologically active chelating and ionophoric agents, including quinolones [ 59 , 60 , 61 ], quinazolines [ 62 , 63 , 64 ], and thiosemicarbazones [ 65 , 66 , 67 , 68 ]. More recently, we have investigated terpyridines (Tpy) that possess strong chelating activity and potential for development [ 69 ].…”
Section: Should We Have Complexes With Terpyridines?mentioning
confidence: 99%